Whole-Genome and Transcriptome Sequencing of Phlebopus portentosus Reveals Its Associated Ectomycorrhizal Niche and Conserved Pathways Involved in Fruiting Body Development - Wan, Jia-Ning; Li, Yan; Guo, Ting; Ji, Guang-Yan; Luo, Shun-Zhen; Ji, Kai-Ping; Cao, Yang; Tan, Qi; Bao, Da-Peng; Yang, Rui-Heng (Frontiers in Microbiology, 2021)
Phlebopus portentosus (Berk. and Broome) Boedijin, a widely consumed mushroom in China and Thailand, is the first species in the order Boletaceae to have been industrially cultivated on a large scale. However, to date, the lignocellulose degradation system and molecular basis of fruiting body development in P. portentosus have remained cryptic. In the present study, genome and transcriptome sequencing of P. portentosus was performed during the mycelium (S), primordium (P) and fruiting body (F) stages. A genome of 32.74 Mb with a 48.92% GC content across 62 scaffolds was obtained. A total of 9,464 putative genes were predicted from the genome, of which the number of genes related to plant cell wall-degrading enzymes was much lower than that of some saprophytic mushrooms with specific ectomycorrhizal niches. Principal component analysis of RNA-Seq data revealed that the gene expression profiles at all three stages were different. The low expression of plant cell wall-degrading genes also confirmed the limited ability to degrade lignocellulose. The expression profiles also revealed that some conserved and specific pathways were enriched in the different developmental stages of P. portentosus. Starch and sucrose metabolic pathways were enriched in the mycelium stage, while DNA replication, the proteasome and MAPK signaling pathways may be associated with maturation. These results provide a new perspective for understanding the key pathways and hub genes involved in P. portentosus development.